Maturation of Social-Vocal Communication in Prairie Vole (Microtus ochrogaster) Pups - Warren, Megan R.; Campbell, Drayson; Borie, Amélie M.; Ford, Charles L.; Dharani, Ammar M.; Young, Larry J.; Liu, Robert C. (Frontiers in Behavioral Neuroscience, 2022)
Impairments in social communication are common among neurodevelopmental disorders. While traditional animal models have advanced our understanding of the physiological and pathological development of social behavior, they do not recapitulate some aspects where social communication is essential, such as biparental care and the ability to form long-lasting social bonds. Prairie voles (Microtus ochrogaster) have emerged as a valuable rodent model in social neuroscience because they naturally display these behaviors. Nonetheless, the role of vocalizations in prairie vole social communication remains unclear. Here, we studied the ontogeny (from postnatal days [P] 8 to 16) of prairie vole pup ultrasonic vocalizations (USVs), both when isolated and when the mother was present but physically unattainable. In contrast to other similarly sized rodents such as mice, prairie vole pups of all ages produced isolation USVs with a relatively low fundamental frequency between 22 and 50 kHz, often with strong harmonic structure. Males consistently emitted vocalizations with a lower frequency than females. With age, pups vocalized less, and the acoustic features of vocalizations (e.g., duration and bandwidth) became more stereotyped. Manipulating an isolated pup’s social environment by introducing its mother significantly increased vocal production at older (P12-16) but not younger ages, when pups were likely unable to hear or see her. Our data provide the first indication of a maturation in social context-dependent vocal emission, which may facilitate more active acoustic communication. These results help lay a foundation for the use of prairie voles as a model organism to probe the role of early life experience in the development of social-vocal communication.